Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acsami.9b21507
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Metal–Organic Framework MIL-100(Fe) on the Surface of BiVO4: A New Platform for Enhanced Visible-Light-Driven Water Oxidation

Abstract: The development of new dual functional photocatalysts is highly desirable for conversion and storage of solar energy. Herein, we first constructed hierarchical structure MIL-100(Fe)@BiVO 4 in situ growing MIL-100(Fe) nanoparticles (NPs) on the surface of decahedron BiVO 4 under mild hydrothermal conditions. The as-synthesized hybrid nanostructure is unambiguously determined using a series of characterization methods. These results demonstrate that the ultra-tiny MOF MIL-100(Fe) particles are immobilized on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…[ 33 ] The elemental mapping images of the 7% (Co–WS 2 )/CZS sample are shown in Figure 2d–i; Cd, Zn, S, W, and Co elements are homogeneous distribution over the entire area of the 7% (Co–WS 2 )/CZS sample, indicating the uniform loading of the CZS nanoparticles on the surface of Co–WS 2 and no other impurity substances existing in the composite. [ 34 ] The concentration of Co is 0.093 mg L −1 by inductively coupled plasma optical emission spectrometer (ICP–OES) measurement (Table S2, Supporting Information). In a word, all of the results suggest that CZS NPs with uniformly dispersed Co–WS 2 through the electrostatic self‐assembly method have high crystallinity and well‐defined morphology.…”
Section: Resultsmentioning
confidence: 99%
“…[ 33 ] The elemental mapping images of the 7% (Co–WS 2 )/CZS sample are shown in Figure 2d–i; Cd, Zn, S, W, and Co elements are homogeneous distribution over the entire area of the 7% (Co–WS 2 )/CZS sample, indicating the uniform loading of the CZS nanoparticles on the surface of Co–WS 2 and no other impurity substances existing in the composite. [ 34 ] The concentration of Co is 0.093 mg L −1 by inductively coupled plasma optical emission spectrometer (ICP–OES) measurement (Table S2, Supporting Information). In a word, all of the results suggest that CZS NPs with uniformly dispersed Co–WS 2 through the electrostatic self‐assembly method have high crystallinity and well‐defined morphology.…”
Section: Resultsmentioning
confidence: 99%
“…fabricated the MIL‐100(x)@BiVO 4 (x = Fe or Cr) composites photocatalysts for oxygen evolution. [ 297 ] The UV–vis diffuse reflectance spectra exhibited that the as‐prepared MIL‐100(Fe)@BiVO 4 photocatalyst has a wider visible light absorption range than MIL‐100(Cr)@BiVO 4 and BiVO 4 ( Figure a) suggesting the remarkable enhancement of the light absorption ability. As a result, the MIL‐100(Fe)@BiVO 4 photocatalyst also showed a higher photocatalytic O 2 evolution rate than other samples under the visible light irradiation (Figure 14b) due to the rapid photogenerated electron separation and transfer between BiVO 4 and MIL‐100(Fe) (Figure 14c).…”
Section: The Photocatalysis Applications Of the Mofs‐based Compositesmentioning
confidence: 99%
“…Unlike for photocatalytic hydrogen production and CO2RR, there have been many studies about the application of MOFs as co-catalysts for photocatalytic water oxidation. For example, Han et al 155 reported the deposition of MIL-100 with different metal nodes (MIL-100(M), where M is Fe or Cr) on a porous BiVO 4 nanoparticle (x%-MIL-100(Fe) @BiVO 4 , where x is the weight percentage of the MOF and can be 2, 4, 8, or 12) (Fig. 13a).…”
Section: Mofs As Photosensitizersmentioning
confidence: 99%